Spatial and Temporal Response of Vegetation and Production of Crops to Climate in Rajasthan, India - K. Rajendram; N. R. Patel (Research Advances in Environment, Geography and Earth Science Vol. 4, 2024)
Agricultural activities are chiefly influenced by the weather and climate. The success or failure of crops mainly under rain-fed conditions in arid and semi-arid regions is closely associated with climate variability. Drought is one of the worst natural calamities that affect major parts of India, mainly in the desert states of Rajasthan recurrently and creates innumerable problems immediately or over time as the economy experiences adverse impacts. In this study, long-term NOAA-AVHRRGIMMS3G (1983-2011) Normalize Difference Vegetation Index (NDVI) time trends were used as a proxy for Net Primary Production (NPP). Monthly rainfall data sets have been collected from the Indian Meteorology Department (IMD) and the Department of Revenue for the period from 1983-2011 for 102 rain gauge stations in Rajasthan. The vegetation greenness in Rajasthan has an increasing trend in the recent decade, these positive anomalies have been noticed from 1996 onwards, however, they may vary at a regional scale. In the 2000 drought, an extreme value of SPI reached up to -3.69 in September and –2.84 in August, which exhibits the severity of drought conditions. Generally, the station belongs to the desert districts of Jaisalmer, Bikaner, and Churu having extreme negative SPI during drought years and moderate anomaly in normal years. This study has demonstrated that there is a direct relationship between rainfall, vegetation, and crop growth. This study found that the spatial and temporal variations of NDVI are closely linked with precipitation and there is a strong association between rainfall anomaly and NDVI anomaly.